Diasporic Synergies: Conceptualizing African Entrepreneurship Based Upon Trans-Local Networks. Issue 1 (2nd January 2019) - Griffin-El, Eliada Wosu; Olabisi, Joy
ABSTRACT: This paper offers a theorization of African diaspora venture creation. We postulate that the motivation for forming trans-local networks – to offer security when socially vulnerable or to pursue business opportunities – mediates the relationship between the habitus of diasporic entrepreneurs and the market-orientation of their venture creation. We extend the theorization by asserting that the compositional diversity and resulting informational redundancy of the network varies depending on the motivation for its formation. This network attributes influence whether the venture is purposed to focus inwardly on the host country market, or outwardly toward contributing to the sustainability of the home country market.